2021
DOI: 10.3390/economies9020056
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Firm R&D in Creating Product and Process Innovation: Empirical Evidence from Norway

Abstract: Government funding actively engages in private R&D investment to enhance firm innovation. At the same time, firms are forced to find additional sources of competitive advantage, e.g., through cooperation based on the triple- or quadruple-helix principles. This paper analyses whether government funding and cooperation based on the triple-helix and quadruple-helix principles spur firms’ product and process innovation rather directly or indirectly, taking into account the role of firms R&D. For this purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 88 publications
2
9
0
Order By: Relevance
“…We found that IPR does not have a significant effect in all quantile period. We firmly confirmed that it is due to the level of economic development in each period and the funding for R&D activities to undertake innovation (Prokop & Stejskal, 2019;Sein & Prokop, 2021). Additionally, we could see the variation of the effect of other variables.…”
Section: Discussionsupporting
confidence: 75%
“…We found that IPR does not have a significant effect in all quantile period. We firmly confirmed that it is due to the level of economic development in each period and the funding for R&D activities to undertake innovation (Prokop & Stejskal, 2019;Sein & Prokop, 2021). Additionally, we could see the variation of the effect of other variables.…”
Section: Discussionsupporting
confidence: 75%
“…Second, talent policy support allows enterprises to access policy resources. Enterprises that receive talent policy support are often more likely to gain the government's trust, and the government, for its part, is more inclined to extend policy support to such enterprises to save on the costs associated with prior inspection, in-process supervision, and post-assessment (Kleer, 2010;Sein and Prokop, 2021). For example, the acquisition of R&D subsidies or tax incentives can reduce the innovation risk to enterprises or minimize R&D costs (Colombo et al, 2013;Jourdan and Kivleniece, 2017;Chen et al, 2019b).…”
Section: Talent Policy and Enterprise Technology Innovationmentioning
confidence: 99%
“…According to business model innovation theory [39], if incumbents want to survive and create lean value, at first, they should understand the current business model and focus on people and their relationships and behaviors. Business process innovation deploys a novel and considerably enhanced production process and distribution mechanism [40]. Another study proposes a framework of dynamic capabilities that organizations can use for developing digital process innovation [41].…”
Section: The Current State Of the Artmentioning
confidence: 99%